Finite plastic deformation of crystalline solids - Havner, K. S. ([S.l.] : Cambridge University Press, 1992)
This book reviews and interrelates a large number of theoretical and experimental contributions to the research on finite plastic deformation of single crystals and polycrystalline metals made during the past quarter century. An overall theoretical framework for investigation of large strains in crystalline materials is presented that enables the blending of contemporary and earlier experimental research with modern concepts in solid mechanics. Professor Havner has provided a historical perspective throughout including accurate attribution of ideas and emphasis on pioneering studies, beginning with G. I. Taylor and the German researchers in the 1920s. Early chapters deal with single crystals, including extensive analyses of particular experimental configurations. Then connections between single crystals and polycrystalline material behavior are considered. Necessary background to the most general theoretical sections is presented in an appendix and approximately 200 references to the primary scientific literature are included.